Ultra-low Voltage Low Power Active-RC Filters and Amplifiers for Low Energy RF Receivers - Severo, Lucas Compassi; Van Noije, Wilhelmus Adrianus Maria; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book presents innovative strategies to implement ultra-low voltage (ULV) and low power active circuits used in low energy RF receivers. The authors demonstrate that the use of single-stage amplifiers with the input negative transconductance compensation is a key strategy to allow the operation at low voltage levels with reduced power dissipation. Also, some design methodologies, based on the CMOS transistor operation point, are analyzed and a powerful design methodology is described for this kind of circuit. Readers will be enabled to implement the techniques described to design communication circuits with low power dissipation, useful in a variety of applications, including IoT/IoE devices. Discusses in detail ultra-low voltage communication circuit design for low energy RF receivers; Describes circuits that are compatible with the low-cost well-established, submicron CMOS processes; Presents a novel and intuitive circuit design methodology to implement the described techniques.
Introduction -- ULV Analog Circuit Design -- Single-Stage Amplifiers and Compensation Techniques -- Design Methodology for ULV Analog Circuits -- Experimental Results -- Conclusion.
Keywords: Electronic circuits; Telecommunication; Electronics; Electronic Circuits and Systems; Microwaves, RF Engineering and Optical Communications; Electronics and Microelectronics, Instrumentation; Low voltage integrated circuits; Radio frequency integrated circuits